Instrumen penilaian kualiti garis panduan media pengajaran untuk tablet skrin sentuh (Q-Qguide) - Hussain, Hashiroh; Shiratuddin, Norshuhada (Universiti Malaya, 2017)
The main aim of this study is to determine the validity and reliability of a questionnaire which evaluates the design guideline of instructional media creation with DST concept (MPBPD) for touch screen tablet.The development of the instrument (Q-Qguide) involves content analysis from previous studies on digital media of guide line.Pilot study is conducted to ensure the feasibility of the real study which involved 147 respondents from the Institute of Teacher Education (ITE).The validation of the instrument is determined by face and content validity by seven experts,meanwhile construct analysis with statistical test.Five items and one construct are omitted in the analysis: two items in the face and content validity and three items using exploratory factor analysis (EFA).The reliability of the instrument is analyzed using Cronbach Alpha test which falls between 0.88 and 0.93. Overall findings indicate that there are 32 items with six constructs namely usefulness, ease to use, easy to understand, applicability, tablet interaction and quality which are appropriate instrument to evaluate the quality of the guideline. This study will yield the policy makers or researchers of the Ministry of Education (MOE) to apply the instrument for evaluating guideline from any instructional media.